Імміграційні програми сучасної ФРН - Фем’як, С. В.; Femiak, S. V. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Визначено особливості політики ФРН щодо регулювання імміграційних потоків. Проаналізовано основні програми для іноземців в сфері імміграційної політики. Розглянуто способи переїзду громадян інших країн до Німеччини. The features of the Policy of Federal Republic of Germany on regulating of the immigration flows are determined. The basic programs for the foreigners in the field of immigration policy are analyzed. The methods of moving of the citizens of other countries to Germany are reviewed.
The Immigration Programs of Modern Federal Republic of Germany
Keywords: іммігрант; імміграційна політика; програми для іноземців у галузі імміграційної політики; immigrant; immigration policy; programs for the foreigners in the field of immigration policy